Freshwater mollusks of the Priplotinny Ples Reach, the Kuibyshev Reservoir (middle Volga River, Russia) - Mikhailov, R A (IOP conference series. Earth and environmental science, 2021)
In September 2020, the fauna of mollusks was studied at the Priplotinny Ples Reach of the Kuibyshev Reservoir, the Volga River, Russia. In total, 23 taxa were registered, including four invasive species. Extrapolating of the species richness, taking into account the sampling effort, allowed to assess the estimated species pool according to the Chao 2 algorithm. Bivalve mollusks predominated in the studied area. The mollusks Dreissena (Pontodreissena) bugensis and Dreissena (Dreissena) polymorpha have been found most frequently at the study sites. Both abundance and biomass varied in wide range, as 391 ± 325 ind. m −2 and 256.693 ± 228.355 g m −2 , respectively. The complex of dominant species was mainly represented by alien mollusks. The type of bottom sediment was a significant ecological factor (p ≤ 0.05) that determined the distribution of mollusks at the Priplotinny Ples Reach. The water quality of the study area was assessed by bioindication method according to the composition and structure of the mollusk fauna, formed mainly by species of European and European-West Siberian ranges.